2014
DOI: 10.1155/2014/752312
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric HIV Long-Term Nonprogressors

Abstract: Patients infected with HIV are best categorized along a continuum from rapid progressors to HIV long-term nonprogressors. Long-term nonprogressors (LTNPs) are those in which AIDS develop many years after being infected with HIV, often beyond the 10-year mark, and represent 15–20% of the HIV infected patients. Many of these patients are able to control their infection and maintain undetectable viral loads for long periods of time without antiretroviral therapy. After a comprehensive literature search, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Compared to adults, children infected with HIV-1 generally progress to AIDS faster, with children in sub-Saharan Africa progressing faster than those in developed countries [ 3 , 4 ]. However, in some cases, children have remained asymptomatic through childhood into adolescence without treatment [ 5 , 6 ]. Several host and viral factors reportedly play roles in disease progression [ 1 , 7 , 8 ], but such findings remain inconclusive especially in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to adults, children infected with HIV-1 generally progress to AIDS faster, with children in sub-Saharan Africa progressing faster than those in developed countries [ 3 , 4 ]. However, in some cases, children have remained asymptomatic through childhood into adolescence without treatment [ 5 , 6 ]. Several host and viral factors reportedly play roles in disease progression [ 1 , 7 , 8 ], but such findings remain inconclusive especially in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…cohort studies in the USA and Europe approximated the prevalence to 5-8%. [20] Warszaski et al found 2% among studied French children, [16] but there is no data on the population of paediatric patients who are LTNPs in Nigeria. This should be researched.…”
Section: Annals Of Health Research Volume 6 Issue No 2 2020__________...mentioning
confidence: 99%
“…In 2021, UNAIDS estimates indicated that 150,000 new HIV infections and 99,000 deaths occurred among African children [ 1 ]. Before the initiative of universal antiretroviral therapy (ART), it was widely noted that some children would remain AIDS-free for more than 10 years and could maintain normal-for-age clusters of differentiation (CD4 + ) T-cell counts [ 2 ] – so-called long-term nonprogressors (LTNP). Children capable of controlling HIV infection present the opportunity for unique insights into the natural host immune responses, which could be essential for the development of novel therapeutics and vaccines [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in adults, vertical HIV infection in pediatric cohorts provides a distinct advantage in estimating progression-free survival. The majority of infections occur (or are detectable) within 45 days of birth, with the remaining instances typically linked to breastfeeding or maternal seroconversion during breastfeeding [ 2 , 4 , 5 ]. Given the temporally fewer yet measurable childhood exposures [ 6 ], pediatric cohorts offer a valuable opportunity to accurately determine the proportion of LTNP.…”
Section: Introductionmentioning
confidence: 99%